Agricultural Practices and Climate Resilience: Case Study in Vietnam - Tuan, Hoang (International Journal of Climatic Studies, 2024)
Purpose: To aim of the study was to analyze agricultural practices and climate resilience: case study in Vietnam. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In Vietnam, agricultural practices significantly enhance climate resilience amidst growing climate variability. Diversified cropping systems and climate-smart techniques like conservation agriculture and agroforestry help mitigate climate-related risks by spreading vulnerabilities and improving soil health and water retention. Promoting resilient crop varieties and livestock breeds further reduces susceptibility to pests, diseases, and extreme weather events. Integrating these strategies into agricultural policies is vital for ensuring food security and sustainability in Vietnam's changing climate. Unique Contribution to Theory, Practice and Policy: Social-Ecological Systems Theory (SES), Adaptive Capacity Theory & Political Ecology Theory may be used to anchor future studies on agricultural practices and climate resilience: case study in Vietnam. Encourage diversification of crops and livestock to increase resilience to climate variability. Promote mixed cropping, agroforestry, and integrated livestock-crop systems, which enhance biodiversity, soil fertility, and pest resilience. Develop and implement policies that support climate-resilient agriculture.